Investigation Of Structure-Activity Relationships With Molecular Docking For Some Antiepileptic Drugs And Voltage-Gated Calcium (CaV) Channels - Çakmak, Esra Nur; Gür, Mahmut; Kiran, Bayram (Kastamonu University, 2022)
In the study, the active drugs molecules used in the treatment of convulsive seizures occurring in epilepsy disease were used. These molecules; Vigabatrin, Lokosamidin, Zonisamide, Oxcarbazepine, Levetiracetam, Tiagabin, Topiramate, Lamotrigine, Gabapentin, Felbamate, Ethosuximide, Valproic Acid, Mesuximide, Ethotoin, Primidone, Trimethadion, Phenytoin, Remasemide, Mephenytoin. These molecules have been selected considering the physiopathological mechanisms of action of epilepsy. Since the selected molecules are used as a potential antiepileptic agent, they were deemed suitable for molecular insertion studies. In addition, voltage-gated calcium channels, which play an important role in epilepsy, are emphasized. Voltage-gated calcium channels (CaV) act by providing the flow of Ca+ ions during the action potential that triggers seizure formation, and among the ten subtypes of voltage-gated calcium (CaV) channels, CaV3.1- CaV3.3, T-type or abnormal activities are associated with epilepsy, psychiatric form the associated low-voltage-activated subfamily. For this reason, the PDB ID: 6KZP receptor, which acts as an antagonist according to its activity on the channel in the formation of epileptic seizures, was chosen for the molecular insertion study. As a result of molecular placement studies; Oxcarbazepine and Phenytoin gave the best binding affinity for 6KZP with a value of -7.5 kcal/mol. Other results are in descending order (in kcal/mol); Tiagabine (-7.4), Mesuximide (-7.3), Primidone (-7.1), Remasemide (-7.0), Topiramate (-6.9) Mephenytoin (-6.7), Lomotrigine and Ethotoin (-6.4), Locosamide and Zonisamide (-6.1) , Felbamate (-6.0), Levetiracetam and Gabapentin (-5.4), Esuximide (-5.1), Valproic Acid (-4.9), Trimethadione (-4.7), Vigabatrin (-4.4) determined as.
Keywords: Engineering; Mühendislik; Calcium Channels; Epilepsy; Moleculer Docking; Ligand; Receptor; Drug; 3. Good health